High‐performance ferroelectric based materials via high‐entropy strategy: Design, properties, and mechanism - Yueyun Zhang; Liang Chen; Hui Liu; Shiqing Deng; He Qi; Jun Chen (InfoMat, 2023)
Abstract High‐performance ferroelectric materials are widely used in various electronic devices owing to the function of mutual conversion among different energies, which mainly relates to their special structure gene of polarization configuration. Recent researches show that the high‐entropy strategy has emerged as an effective and flexible approach for boosting physical properties in high‐entropy ferroelectrics via the delicate design of local polarization configurations and other intrinsic effects caused by entropy increment, such as entropy stabilization, lattice disorder, inhibition of grain coarsening, improved mechanical properties, cocktail effect, and so on. In this review, the recent research progress about high‐entropy ferroelectrics has been summarized, especially for the directional design of novel local polarization configurations according to the characteristics of different electrical properties such as high piezoelectricity, high‐efficiency energy storage, and large electrostriction, providing a guidance for designing and exploring more novel local polarization configurations in high‐entropy ferroelectrics for generating higher performance.